Honeycomb-like CuO/ZnO hybrid nanocatalysts prepared from solid waste generated in the organosilane industry. Issue 64 (21st June 2016) - Li, Jing; Liu, Hezhi; Ji, Yongjun; Zhang, Yu; Wang, Guangna; Zhu, Yongxia; Zhong, Ziyi; Hu, Xiao; Su, Fabing
Abstract : Honeycomb-like CuO/ZnO hybrid nanocatalysts prepared from solid waste in organosilane industry exhibited excellent catalytic properties when re-used for dimethyldichlorosilane synthesis. Abstract : We report the preparation of honeycomb-like CuO/ZnO (CZ x / y ) nanocatalysts with CuO nanospheres (NSs) adhered with ZnO nanoparticles (NPs) for the Rochow reaction. The synthesis was carried out via adsorption of Cu 2+ /Zn 2+ ions on carbon black (CB) which acted as both the agglomeration inhibitor and the hard template, and followed by calcination in air. The low cost Cu 2+ /Zn 2+ ions were recovered from the solid waste generated in the organosilane industry via a simple ammonia leaching treatment. The samples were characterized by X-ray diffraction, transmission electron microscopy, scanning electron microscopy, X-ray photoelectron spectroscopy, and temperature-programmed reduction. The as-obtained CZ x / y nanohybrids had a honeycomb-like structure with large voids and openings among the CuO NSs. When re-used as a Cu-based catalyst for the Rochow reaction, the CZ x / y NPs sample with an optimized ratio showed significantly improved dimethyldichlorosilane (M2) selectivity and silicon (Si) conversion as compared with the CuO/ZnO NPs prepared in the absence of CB, discrete CuO or ZnO NPs and the CuO/ZnO NPs with different compositions, mainly due to the unique honeycomb-like structure, smaller crystal size and synergistic electronic effect at the interface between Cu and ZnO in CZ x / y NPs.